The Influence Of English Learning Animation Media On Second Grade Students At State Elementary School 122371 Pematang Siantar - Simanjuntak, Olopai; Sibarani, Imelda Sabrina; Sianipar, Posma; Aritonang, Naomi; Jenetri, Yustina; Siahaan, Windi; Sipayung, Juliana; Damanik, Wulandari; Sagita, Amanda Dwi; Simamora, Rosa (Universitas Negeri Medan, 2024)
This research is entitled